Morphological genetic and biological studies of red palm weevil, rhynchophorus spp. (coleoptera: curculiondae) in Terengganu, Malaysia - Yong, Kah Wai (2016)
The Red Palm Weevil (RPW), Rhynchophorus ferrugineus (Olivier) is the most important pest of various palm species including coconut, date and oil palm in the world. Rhynchophorus ferrugineus is a lethal pest of coconut in Terengganu and sago palm in Sarawak, Malaysia. This study was intended to investigate the morphological, genetic and biological studies of red palm weevil (RPW) which include of two Rhynchophorus morphospecies – R. ferrugineus and R. vulneratus in Malaysia.